Immune-endocrine crossroads: the impact of nuclear receptors in Tuberculosis and Chagas disease - Pérez, Ana R.; Bottasso, Oscar A.; Santucci, Natalia E. (Frontiers in Endocrinology, 2025)
Nuclear Receptors (NRs) comprise a superfamily of proteins with essential roles in cell signaling, survival, proliferation, and metabolism. They act as transcription factors and are subclassified into families based on their ligands, DNA-binding sequences, tissue specificity, and functions. Evidence indicates that in infectious diseases, cancer, and autoimmunity, NRs modulate immune and endocrine responses, altering the transcriptional profile of cells and organs and influencing disease progression. Chronic infectious diseases, characterized by pathogen persistence, are particularly notable for an exaggerated inflammatory process. Unlike acute inflammation, which helps the host respond to pathogens, chronic inflammation leads to metabolic disorders and a dysregulated neuro-immuno-endocrine response. Over time, disturbances in cytokine, hormone, and other compound production foster an unbalanced, detrimental defensive response. This complexity underscores the significant role of ligand-dependent NRs. Tuberculosis and Chagas Disease are two critical chronic infections. The causative agents, Mycobacterium tuberculosis and Trypanosoma cruzi, have developed evasion strategies to establish chronic infections. Their clinical manifestations are associated with disrupted immuno-endocrine responses, pointing to a potential involvement of NRs. This review explores the current understanding of NRs in regulating immune-endocrine interactions within the context Tuberculosis and Chagas Disease. These diseases remain significant global health concerns, particularly in developing countries, highlighting the importance of understanding the molecular mechanisms underlying host-pathogen interactions mediated by NRs.